1988
DOI: 10.1042/bj2520723
|View full text |Cite
|
Sign up to set email alerts
|

A collagen-binding glycoprotein on the surface of mouse fibroblasts is identified as dipeptidyl peptidase IV

Abstract: A dipeptidyl aminopeptidase (DPP) was detected in plasma membranes from normal (3T3) and transformed (3T12) mouse fibroblasts. This enzyme was active in cleaving the prolyl bond in the synthetic dipeptide nitroanilide Gly-Pro-NH-Np, which is a specific substrate for DPP IV (Km 0.63 mM and Vmax 6.1 nmol/min per mg at pH 6.0 and 37 degrees C). However, it did not degrade Pro-NH-Np or other dipeptide nitroanilides such as Gly-Arg-NH-Np or Val-Ala-NH-Np. The enzyme was totally inhibited by di-isopropyl phosphorofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
2
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 46 publications
1
65
2
2
Order By: Relevance
“…Role in Cell Adhesion-As DPPIV was shown to be an adhesion receptor for collagen (15)(16)(17) or fibronectin (18 -20), we have examined whether the inhibitory effect of mAb E19 (against DPPIV) on cellular migration in collagen gels and on gelatin degradation by migratory cells was due to its influence on adhesion activity. In a parallel comparison to integrin adhesion to collagen fibers, whereas mAb E19 (against DPPIV) inhibits cellular migration in collagen gels and gelatin degradation by migratory cells, it does not affect WI38 cell spreading on type I collagen substratum and attachment to collagen substratum (data not shown).…”
Section: Fig 3 Prolyl Peptidase Activities and Dppiv Binding To Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Role in Cell Adhesion-As DPPIV was shown to be an adhesion receptor for collagen (15)(16)(17) or fibronectin (18 -20), we have examined whether the inhibitory effect of mAb E19 (against DPPIV) on cellular migration in collagen gels and on gelatin degradation by migratory cells was due to its influence on adhesion activity. In a parallel comparison to integrin adhesion to collagen fibers, whereas mAb E19 (against DPPIV) inhibits cellular migration in collagen gels and gelatin degradation by migratory cells, it does not affect WI38 cell spreading on type I collagen substratum and attachment to collagen substratum (data not shown).…”
Section: Fig 3 Prolyl Peptidase Activities and Dppiv Binding To Gelmentioning
confidence: 99%
“…DPPIV and seprase are type II transmembrane proteins, with cytoplasmic tails that contain 6 amino acids (aa) followed by a 20-(seprase) or 22-aa (DPPIV) transmembrane domain at the N terminus and a stretch of 200 aa at the C terminus that constitutes a catalytic region with the catalytic serine in a non-classical orientation as compared with serine proteinases such as trypsin and chymotrypsin (13,14). DPPIV has binding capability for collagen (15)(16)(17) and fibronectin (18 -20). In addition, a recent report (21) showed that DPPIV also possesses a seprase-like gelatinase activity and therefore endopeptidase activity, suggesting its involvement in gelatin degradation.…”
mentioning
confidence: 99%
“…Its proteolytic activity leads to inactivation or degradation of these peptides (7,8). DPPIV is involved in diverse biological processes, including cell differentiation, adhesion, immunomodulation, and apoptosis, functions that are critical for controlling neoplastic transformation (7)(8)(9)(10)(11)(12)(13). DPPIV is expressed in normal epithelial cells and melanocytes (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…20 Among the best candidates as physiological substrates are the neuropeptide substance P 21 and several cytokines, such as IL-1, IL-2, and IL-6. 20 Evidence indicates that CD26 may interact with extracellular matrix proteins, [22][23][24][25] suggesting that this molecule is in some way involved in the tissue remodeling process. Most of the functional properties of CD26, and its intermolecular connections, have been elucidated in T lymphocytes, in which CD26 is up-regulated during cell activation.…”
Section: Discussionmentioning
confidence: 99%